Strategi Penyelesaian Soal Cerita Siswa Sekolah Dasar: Analisis Hambatan Belajar Konsep Penjumlahan dan Pengurangan Bilangan Cacah - Syarifah, Mufarrahatus; Suryadi, Didi; Prabawanto, Sufyani (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2023)
This research aims to describe the learning obstacles experienced by students in the concept of addition and subtracting whole numbers through the strategies used in solving word problems. This research is a qualitative descriptive study whose data was taken using tests and interviews. The test was given to 30 grade 3 students from two different elementary schools. Their answers were classified by error type and interviews were conducted to further explore how they arrived at solutions. For additional information, open interviews were conducted with each class teacher. Three types of learning obstacles were occured. The attitude of students who appear to be less confident in determining strategies and unsure of what to do with questions in the form of stories indicates the existence of ontogenic obstacle. Students' success in completing one situation and failing in another situation in the same concept indicates the existence of epistemological obstacle. Students' failure to recognize key words in the story that indicate addition or subtraction situations indicates didactic obstacle.